Mir-513a-3p contributes to the controlling of cellular migration processes in the A549 lung tumor cells by modulating integrin beta-8 expression - Silveira, Marina Bonfogo da [UNESP] (2018)
Lung tumors are a frequent type of cancer in humans and a leading cause of death, and the late diagnostic contributes to high mortality rates. New therapeutic strategies are needed, and the heptapeptide angiotensin-(1-7) [ang-(1-7)] demonstrated the ability to control cancer growth rates and migration in vitro and in vivo. However, the possible use of the heptapeptide in clinical trials demands deeper analyses to elucidate molecular mechanisms of its effect in the target cells. In this study, we investigated relevant elements that control pro-inflammatory environment and cellular migration, focusing in the post-transcription mechanism using lung tumor cell line. In our cellular model, the microRNA-513a-3p was identified as a novel element targeting ITG-beta 8, thereby controlling the protein level and its molecular function in the controlling of migration and pro-inflammatory environment. These findings provide useful information for future studies, using miR-513a-3p as an innovative molecular tool to control lung tumor cell migration, which will support more effective clinical treatment of the patients with the widely used chemotherapeutic agents, increasing survival rates.